Vertical Protection Level Optimization and Availability Analysis for Advanced RAIM - Wang, Ershen; Shu, Wansen; Deng, Xidan; Wang, Zhi; Xu, Song; Wang, Huan (Frontiers in Energy Research, 2022)
With the introducing of global navigation satellite system (GNSS) in aviation, there has been increased dependency on GNSS position. GNSS Multi-constellation services and equipment will remain a solution and the trend for many aircraft’ position in safety. Multi-constellation GNSS can improve robustness and navigation performance. Advanced receiver autonomous integrity monitoring (advanced RAIM, ARAIM) techniques are being developed as an augmentation for use under multi-constellation. ARAIM can allow increased service level globally and provide vertical guidance during the approach phase for aircrafts. Since the traditional ARAIM algorithm uses the average allocation strategy to allocate integrity risk and continuity risk. And the average allocation strategy cannot guarantee that users attain the optimal vertical protection level (VPL), an allocation method based on particle swarm optimization (PSO) algorithm is presented. In the paper, different allocation strategies for integrity and continuity risk are chosen as different particles, and the weighted sum of vertical protection levels corresponding to different fault subsets are selected as the fitness function to optimize allocation strategy and the corresponding VPL. Based on the real GNSS data, the ARAIM algorithm under multi-constellation is analyzed. The experimental results show that the integrity and continuity risk allocation method based on the proposed algorithm is able to optimize the VPL and improve the global availability of ARAIM under multi-constellation. Meanwhile, the results have great reference value on the study of robots positioning.